Development and reliability of the coding system evaluating maternal sensitivity to social interactions with 34- to 36-week postmenstrual age preterm infants - Boissel, Laure; Pinchaux, Emeric; Guilé, Marine; Corde, Pascal; Crovetto, Cécile; Diouf, Momar; Mariana, Charlotte; Meynier, Jonathan; Picard, Carl; Scoury, Daphné; Cohen, David; Benarous, Xavier; et al. (Frontiers in Psychiatry, 2022)
Maternal sensitivity (MS), the ability to perceive and synchronously respond to the social signals (SSs), is affected by prematurity. The development of early supportive psychotherapy to foster MS, before discharge of the infant from the neonatal intensive care unit (NICU) is a major challenge in the prevention of subsequent developmental and mental disorders in the child. There are currently no reliable methods for evaluating MS to social interactions with very to moderate preterm infants. We investigated the reliability of a newly developed procedure for assessing MS in interactions between the mother and her 34- to 36-week postmenstrual age (PMA) preterm infant: the Preterm Infant Coding System for Maternal Sensitivity (PRICOSMAS). Method This study encompassed three steps: testing of the capacity to videorecord SSs in very to moderate preterm infants, selection, by an expert committee, of the recordable and relevant SSs, and investigation of the internal consistency and interrater reliability. The synchronicity between infant and mother's SSs was determined on a 1 s period basis, using ELAN software. Preterm infants born after 25-weeks gestational age (GA) were included while being between 34- and 36-weeks PMA. A perinatal risk inventory score > 10 for the infant precluded from inclusion. Interrater reliabilities were assessed independently by two raters blind to the clinical situation of the mother and infant. Results The resulting PRICOSMAS encompassed two four-item SS sections, one covering the preterm infant's SSs and the other, the mother's SSs. Reliability was assessed on a sample of 26 videorecorded observations for 13 mother-preterm infant dyads. Infants' mean age at birth was 30.4 ± 3.1-weeks GA (range: 26.4–35) and PMA at the time of the test was 34.7-weeks (±0.8). Internal consistency ranged from 0.81 to 0.89. Interrater reliability ranged from substantial to almost perfect (0.73–0.88). Conclusion This study shows that the infants' SSs and MS can be reliably scored in preterm infants as young as 34- to 36-weeks PMA. Our findings suggest that the PRICOSMAS is sufficiently reliable for use, including in NICU, by healthcare professionals or researchers for coding early parent-infant interactions with 34- to 36-week PMA preterm infants.